Present status of implementation of undergraduate curriculum of Bangladesh in selected private medical colleges: Teachers perspectives - Mosaddek, Abu Syed Md; Islam, Md Zakirul; Rahman, Md Faizur; Chaudhury, Habib S; Parvin, Roksana; Khanom, Matira (South East Asia Journal of Public Health, 2013)
DOI: http://dx.doi.org/10.3329/seajph.v1i1.13227 South East Asia Journal of Public Health 2011:1:73-74